2017
DOI: 10.4172/2161-0711.1000504
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude and Practice of Voluntary Blood Donation and Associated Factors among Residents of Birbir Town

Abstract: Blood transfusion is a medical procedure that is designed to provide patients who need blood or blood products to correct a defect. Secure supply of safe blood components, based on voluntary, non-remunerated blood donation is an important national goal to prevent blood shortages. Now a day, in many low and middle income countries, blood supply is critically inadequate. Therefore, the objective of this study was to assess knowledge, attitude, and practice of voluntary blood donation and associated factors among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
3
4
2
Order By: Relevance
“…The similarities between these studies might be due to common low awareness creation regarding blood donation in developing countries. In contrast with the above similarities, finding from this study was higher than the findings from other studies conducted in different cities of Ethiopia; Goba University students in which 18.4%, 21 Adama 17%, 22 Hawasa 14.7%, 23 Birbir 10.6% 24 and Harar 22.6%, 25 and a cross-sectional study conducted among college students in Nepal and Ebony Nigeria 18.1% and 13.3% have ever donated blood, respectively,11,26 of participants ever of population ever donated blood. But the finding of this study was lower than other studies conducted in Chiro town, Eastern Ethiopia, among civil servants 43.6%, 16 medical students in Lahore district 66.9%, and a descriptive study on community members aged 15–50 in Kampala, Uganda, was 33.3% 27,28 , respectively.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The similarities between these studies might be due to common low awareness creation regarding blood donation in developing countries. In contrast with the above similarities, finding from this study was higher than the findings from other studies conducted in different cities of Ethiopia; Goba University students in which 18.4%, 21 Adama 17%, 22 Hawasa 14.7%, 23 Birbir 10.6% 24 and Harar 22.6%, 25 and a cross-sectional study conducted among college students in Nepal and Ebony Nigeria 18.1% and 13.3% have ever donated blood, respectively,11,26 of participants ever of population ever donated blood. But the finding of this study was lower than other studies conducted in Chiro town, Eastern Ethiopia, among civil servants 43.6%, 16 medical students in Lahore district 66.9%, and a descriptive study on community members aged 15–50 in Kampala, Uganda, was 33.3% 27,28 , respectively.…”
Section: Discussioncontrasting
confidence: 98%
“…The proportion of participants whose ever donated blood once in their life was higher than the finding from the study conducted in Birbir town among the general population where only 6.4% of participants ever donated blood once in their life. 24 The discrepancy in these findings might be because civil servants had more chance to participate in blood donation campaigns and have access to information more than the general population. In contrast, it was lower than the result from the study done on medical students in Solan, North India, in which 67.7% 32 of them ever donated blood.…”
Section: Discussionmentioning
confidence: 96%
“…The study finding showed that life time blood donation among civil servants was 43.6% which was consistent with cross sectional study conducted among workers in Topiwala and descriptive study conducted in Vellore District, Tamilnadu, South India where 47.7% and 49% respectively. In contrast it was higher than the other studies conducted in different cities of Ethiopia, Addis Ababa 32.6%, Harar 22.6%, Bahirdar 10.6% and Aman 26.4%, (1,3,7,9,10,13). Possible reason for this discrepancy may be due to variation in desired characteristics and the study populations.…”
Section: Discussioncontrasting
confidence: 58%
“…The sample size was calculated based on 5% precision and a 95% confidence level with an infinite population using a single proportion calculation where 38.3% of the population had adequate knowledge (8). A minimum sample size of 399 was required.…”
Section: Methodsmentioning
confidence: 99%
“…Blood safety knowledge levels vary among developing countries. Researchers have found that, in Southern Ethiopia, only 38% of the population have adequate knowledge (8). Important information, such as the association of TTIs with permanent deferrable risk behaviours (multiple sexual partners, male-to-male sex and intravenous drug abuse) and temporary deferrable risks (tattoos or acupuncture in the past six months, tooth extraction in the past 24 h and staying with family members who have HBV or HCV), has not previously been assessed among blood donors (9).…”
Section: Introductionmentioning
confidence: 99%